A contribution to the taxonomy of the genus Pentacentrus Saussure (Orthoptera: Gryllidae: Pentacentrinae) - Li, Ruotong; Xu, Fei; Liu, Hao-Yu (Zootaxa, 2019)
A key and a distribution map of the Chinese species of the genus Pentacentrus Saussure are provided. Pentacentrus dulongjiangensis sp. nov. is described from Yunnan, China. The new species is similar to P. medogensis Zong, Qiu & Liu, 2017 from Xizang, China, but differs from the latter by the shape of male genitalia and the color of the tegmina.